2011
DOI: 10.1209/0295-5075/96/28001
|View full text |Cite
|
Sign up to set email alerts
|

Modelling bacterial flagellar growth

Abstract: Lattice models in biological physics PACS 87.16.Ka -Filaments in subcellular structure and processes PACS 87.16.Qp -FlagellaAbstract -The growth of bacterial flagellar filaments is a self-assembly process where flagellin molecules are transported through the narrow core of the flagellum and are added at the distal end. To model this situation, we generalize a growth process based on the TASEP model by allowing particles to move both forward and backward on the lattice. The bias in the forward and backward jump… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
(46 reference statements)
0
22
0
Order By: Relevance
“…The simplest model for flagellin transportation is that partially unfolded flagellins diffuse through the channel in a single-file and then fold at the distal end. Considering this model, Schmitt and Stark used the totally asymmetric simple exclusion process (TASEP) models with open boundary to simulate flagellin transportation and flagellar growth [ 83 ]. TASEP has been applied successfully to study nonequilibrium steady states such as the motion of ribosomes along mRNA, molecular motors along microtubule filaments, or the traffic of the car on the highway.…”
Section: Flagellar Filament Constructionmentioning
confidence: 99%
“…The simplest model for flagellin transportation is that partially unfolded flagellins diffuse through the channel in a single-file and then fold at the distal end. Considering this model, Schmitt and Stark used the totally asymmetric simple exclusion process (TASEP) models with open boundary to simulate flagellin transportation and flagellar growth [ 83 ]. TASEP has been applied successfully to study nonequilibrium steady states such as the motion of ribosomes along mRNA, molecular motors along microtubule filaments, or the traffic of the car on the highway.…”
Section: Flagellar Filament Constructionmentioning
confidence: 99%
“…In contrast, more recently, ( Turner et al, 2000 , 2012 ) labeled Escherichia coli 's pre-existing and newly grown flagellar segments with fluorescent dyes of two different colors and found that the average flagellar growth rate is a constant value independent of the flagellar length. There currently exist different theoretical predictions on the relationship between growth rate and length ( Keener, 2006 ; Schmitt and Stark, 2011 ; Tanner et al, 2011 ; Stern and Berg, 2013 ). Despite this controversy, nearly all existing experimental investigations have been based on population measurements of flagellar length at two different time points at long intervals.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest, that length-dependent depolymerization in combination with polymerization allows a cell to regulate the length of MTs [7,8]. There are by now several theoretical studies addressing length-regulation ranging from MTs [16,17], over actin filaments [18] to fungi [19] and flagellae [20].…”
mentioning
confidence: 96%